KELAYAKAN MEDIA KOMIK BERBASIS KARAKTER PADA SUBMATERI PELESTARIAN LINGKUNGAN KELAS X SMA - Dinda Puspita Sari; Kurnia Ningsih; Eko Sri Wahyuni (EduNaturalia: Jurnal Biologi dan Kependidikan Biologi, 2023)
One of the efforts to build character education for the students can be done through learning media. The purpose of this study was to determine the appropriateness of character-based comics as a medium of learning in the sub-material of environmental conservation. This research is a Research and Development (R&D) with the Borg and Gall model which consists of 5 stages. (1) The potential and problem stage aims to find out the problems and potential solutions to the learning problems. (2) The data collection stage is obtained from the results of observations which are the basis for product design. (3) The product design stage begins with the formulation of objectives based on the syllabus, comic format, synopsis, character selection, and book format. (4) The design validation stage involves 5 validators. (5) The design revision stage is obtained from the suggestions and feedback from the validator therefore it is feasible to use. The results of the validation of character-based comic media obtained Aiken's Vhitung Aiken’s 0,90 > Vtabel Aiken’s 0,80 with a valid category. Therefore, character-based comics in the sub-material of environmental preservation for class X SMA are appropriate to be used as learning media.